Implementasi Pendekatan Pembelajaran Saintifik pada Pembelajaran PPKn di Kelas X - Maradila, Diah Ayu; Wahono, Margi (Civic Education Program, Universitas Negeri Semarang, 2019)
Curriculum 2013 aims to create productive, creative, innovative, affective Indonesian people by strengthening the integration of attitude, skill and knowledge. This curriculum points out scientific approach as the implemented approach in education, especially Civic Education learning. The approach is believed as the best way to develop attitude, skill and knowledge of students.Ã‚Â The objective of this study is to find out the implementations, obstacles, and methods to resolve scientific approachÃ¢â‚¬â„¢s problem in Civic Education learning Class X in SMA Negeri 1 Kradenan. This study uses qualitative methods. The techniques of collecting data are: observation, interview, and documentation. The validity of study is examined by triangulation technique. The techniques of analyzing data are: reduction, presentation and conclusion. This study shows: (1) the implementations scientific approach in Civic Education learning Class X in SMA Negeri 1 Kradenan which are started from planning, implementation of 6M activities (Observing, Questioning, Experimenting, Associating, Communicating, and Creating ), and scoring. This learning method involves introduction, main activity, and conclusion. (2) the obstacles of implementing scientific approach in Civic Education learning are experienced by Civic EducationÃ¢â‚¬â„¢Ã‚Â teachers and students. There are some obstacles in every steps of the scientific approach, they are: observing, questioning, collecting information, reasoning, and communicating. (3) teachers implement some methods to overcome obstacles of implementing scientific approach in Civic Education learning. The methods which are implemented in every step are: observing, questioning, collecting information, reasoning, and communicating.